The effect of the rations containing different ratios of urea on rumen and blood metabolites of angora goats - Şule Kaya; Mehmet Kocabatmaz (Eurasian Journal of Veterinary Sciences)
The aim of this study was to investigate the effects of urea which is supplied to the basal ration containing 75 % of wheat straw and 25 % of concentrate feed as 2 % (group i) and % 4 (group ii) of concentrate feed on the saliva, rumen fluid and blood parameters of Angora goats. In this study 3 male Angora goats at the age of 1.5 years were used according to the 3X3 Latinsquare design. The samples were taken before feeding, 2nd and 6th hours after feeding. The rumen ammonia nitrogen of the group ii at the all sampling times (P<0.01) and the blood urea nitrogen of the same group increased (p<0.01) compared with other groups at sampling times after feeding.The pH of rumen fluid of the group i and the control animals decreased (p<0.01) after feeding. The urea nitrogen of saliva (respectively p<0.05, p<0.01) and the numbers of the rumen fluid protozoa (p<0.01) increased in 2 % and %4 urea supplied groups than that control group at before and after feeding samples.The saliva pH was higher in the group ii compared with the control group at 2nd sampling time (p<0.05).The blood ammonia nitrogen concentration of the same group was the highest in other groups at the same sampling time. The total blood serum protein concentration of the control group increased compared with urea supplied groups (p<0.01). The blood glucose concentration of the group I was higher than the control group at the 2nd sampling time (p<0.05).There weren't significanl differences among the groups and sampling times considering estimated asetic and propionic acid values. The concentration of butiric acid of the group I was the highest in the groups at before feeding samples and was higher than the control group at 3rd sampling time.The concentration of the total volatile fatty acids wasn't different among the groups. in conclusion; the decreased rumen fluid pH and the increased butiric acid concentration of group I, indicated that there were positive effect on the use of rumen ammonia nitrogen and the energy requirement of rumen epitelia and synthesis of milk protein and glucose compared with other groups. Therefore, the supply of %2 of urea to the basal ration containing % 25 of concentrate feed was suggested to the farmers.